(untitled) (Bangladesh Journal of Botany, 2019)
An intraspecific hybridization programme among Cucumis species involving eight genetically diverse parents of C. melo L. varietal group viz., IC-0599709, Punjab Sunehri, Pusa Madhuras, Kashi Madhu (C. melo L.), AHK-119 (C. melo var. callosus), AHLM-2 (C. melo var. utilissimus), AHS-82 (C. melo var. momordica) and Arya-1 (C. melo var. chate) were undertaken. Among the dessertic F1 hybrids, IC-0599709 × Punjab Sunehri resulted best with respect to first fruit harvest (73.33 days), fruit weight (938.00 g), fruit diameter (11.90 cm), flesh thickness (3.07 cm), total soluble solids (9.73%) and flesh colour (salmon orange). F2 population of AHK-119 × Kashi Madhu produced maximum number of marketable fruits per plant (11.2) weighing 350.00 g in 86.1 days. It was also found to be tolerant to high temperature. The F2 population of AHK-119 × Kashi Madhu were found to be tolerant to high temperature. The existing variability among the parents, intra-specific crosses and segregating generations for fruit (size, shape, colour), yield and quality parameters could be exploited to develop new segregants with desirable traits.